2021
DOI: 10.1101/2021.01.18.427137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kinetic analysis of ASIC1a delineates conformational signaling from proton-sensing domains to the channel gate

Abstract: Acid-sensing ion channels (ASICs) are neuronal Na+ channels that are activated by a drop in pH. Their established physiological and pathological roles, involving fear behaviors, learning, pain sensation and neurodegeneration after stroke, make them promising targets for future drugs. Currently, the ASIC activation mechanism is not understood. Here we used voltage-clamp fluorometry (VCF) combined with fluorophore-quencher pairing to determine the kinetics and direction of movements. Molecular dynamics simulatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…A study with toadfish ASIC1 also found a competition between H + and Ca 2+ and concluded, based on a detailed functional analysis, that this channel is activated by an allosteric mechanism and not by a release of Ca 2+ block [32]. A further indication that in ASIC1a, activation involves conformational changes comes from voltage clamp fluorometry studies that detected conformational changes associated with channel opening [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…A study with toadfish ASIC1 also found a competition between H + and Ca 2+ and concluded, based on a detailed functional analysis, that this channel is activated by an allosteric mechanism and not by a release of Ca 2+ block [32]. A further indication that in ASIC1a, activation involves conformational changes comes from voltage clamp fluorometry studies that detected conformational changes associated with channel opening [33,34].…”
Section: Discussionmentioning
confidence: 99%